Wzrost efektywności jako przesłanka tworzenia więzi międzyorganizacyjnych - Czakon, Wojciech (Efficiency Rises as Incentive to Create Interorganizational Relationships, 2006)
Interorganizational linkages encompass many cooperation forms between distinct entities. Efficiency based motives are seen as major relationship creation reasons. Synergies, privileged exchange conditions or value creation growth seem to be specific incentives. Nevertheless many interorganizational linkages appear to be irrational from the efficiency point of view. Competitive rationality is necessary to fully explain such behaviors. Companies strive to improve competitive position or to protect it. This leads to the conclusion that linkages are created for both reasons: efficiency and competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 244-250